Collagen matrix as a tool in studying fibroblastic cell behavior - Kanta, Jiří (Cell adhesion & migration, 2015)
Type I collagen is a fibrillar protein, a member of a large family of collagen proteins. It is present in most body tissues, usually in combination with other collagens and other components of extracellular matrix. Its synthesis is increased in various pathological situations, in healing wounds, in fibrotic tissues and in many tumors. After extraction from collagen-rich tissues it is widely used in studies of cell behavior, especially those of fibroblasts and myofibroblasts. Cells cultured in a classical way, on planar plastic dishes, lack the third dimension that is characteristic of body tissues. Collagen I forms gel at neutral pH and may become a basis of a 3D matrix that better mimics conditions in tissue than plastic dishes.
Keywords: extracellular signal-regulated kinase; FAK; Animals; myofibroblasts; transforming growth factor β 1; TIMP; granulation tissue; HSC; extracellular matrix; tissue inhibitor of metalloproteinases; TNF-α; cell culture; myofibroblasts; MKL1; Fibroblasts; substrate stiffness; Collagen; integrins; collagen; lidé; kolagen; α-smooth muscle actin; 3D; AP-1; focal adhesion kinase; GT; megakaryoblastic leukemia 1; MMP; fibroblasty; kultivované buňky; extracelulární matrix; c-Jun N-terminal kinase; MFB; fibroblasts; tumor necrosis factor α; Cells, Cultured; 3-dimensional; TGFβ-1; fibronectin; metalloproteinases; metalloproteinases; NF-κB; hepatic stellate cells; JNK; Extracellular Matrix; extracellular matrix; ERK; cell proliferation; zvířata; activator protein 1; ECM; polyethylene glycol; α-SMA; phosphatidylinositide 3-kinase/Ak strain transforming; PEG; nuclear factor kappa B; PI3K/Akt; Humans